Pengembangan Aplikasi berbasis Android Sistem Presensi dengan menggunakan Validasi Koordinat Lokasi dan Foto Selfie di PT. Bintang Mas Glassolutions - Tom Ian Buana; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
There are still many manual attendance systems found in companies that exist today, including PT.Bintang Mas Glassolutions which still uses a presence system that is quite behind in terms of technology that has developed, namely by using initial presence on a paper. The obstacles that still occur in the use of attendance above are the impractical process of employee attendance that has to walk to another room and less practical in terms of searching data when the company will see the performance of employees with the attendance system. Based on these problems, an android-based online presence system was created using location coordinate validation and selfie photos at PT. Bintang Mas Glassolutions. In the needs analysis stage in this study produced 12 functional requirements, and 2 non-functional requirements, and 2 actors who will use the system, namely admin and employees. After getting the results of the needs analysis, then make a design for the system with reference to the results of the needs analysis obtained. In the architectural design of the system is described by making system architecture drawings, algorithm design with flowcharts and pseudocode, system design with activity diagrams, sequence diagrams, and class diagrams, database design with tables of the system database structure to be built, and interface design is described in mockup form. This study uses the waterfall development method, uses the Flutter framework, and the dart programming language at the implementation stage. System testing using Blackbox Testing with 100% valid results, usability testing using SUS with a final score of 84.25 grade A, and compatibility testing by installing the application to several devices with different Android versions with 100% valid results.